Tissue patrol by resident memory CD8+ T cells in human skin - Dijkgraaf, Feline E.; Matos, Tiago R.; Hoogenboezem, Mark; Toebes, Mireille; Vredevoogd, David W.; Mertz, Marjolijn; van den Broek, Bram; Song, Ji-Ying; Teunissen, Marcel B. M.; Luiten, Rosalie M.; Beltman, Joost B.; Schumacher, Ton N. (Nature immunology, 2019)
Emerging data show that tissue-resident memory T (T RM ) cells play an important protective role at murine and human barrier sites. T RM cells in the epidermis of mouse skin patrol their surroundings and rapidly respond when antigens are encountered. However, whether a similar migratory behavior is performed by human T RM cells is unclear, as technology to longitudinally follow them in situ has been lacking. To address this issue, we developed an ex vivo culture system to label and track T cells in fresh skin samples. We validated this system by comparing in vivo and ex vivo properties of murine T RM cells. Using nanobody labeling, we subsequently demonstrated in human ex vivo skin that CD8 + T RM cells migrated through the papillary dermis and the epidermis, below sessile Langerhans cells. Collectively, this work allows the dynamic study of resident immune cells in human skin and provides evidence of tissue patrol by human CD8 + T RM cells. Tissue-resident memory T (T RM ) cells have been studied mainly in mouse models. Schumacher and colleagues have developed an imaging technology to track in real time skin-resident human CD8 + T RM cells in situ.